The Macro-Autophagy-Related Protein Beclin-1 Immunohistochemical Expression Correlates With Tumor Cell Type and Clinical Behavior of Uveal Melanoma - Broggi, Giuseppe; Ieni, Antonio; Russo, Daniela; Varricchio, Silvia; Puzzo, Lidia; Russo, Andrea; Reibaldi, Michele; Longo, Antonio; Tuccari, Giovanni; Staibano, Stefania; Caltabiano, Rosario (Frontiers in Oncology, 2020)
Uveal melanoma, in spite of its rarity, represents the most common primitive intraocular malignant neoplasm of the adults; it affect choroid, ciliary bodied and iris and remains clinically silent for a long time, being accidentally discovered by routine ophthalmic exams. Prognosis of uveal melanoma is poor and frequently characterized by liver metastases, within 10-15 years from diagnosis. Autophagy is a multi-step catabolic process by which cells remove damaged organelles and proteins and recycle nutrients. It has been hypothesized that in early stages of tumorigenesis autophagy has a tumor suppressor role while, in more advanced stages, it may represent a survival mechanism of neoplastic cells in response to stress. Several proteins related to autophagy cascade have been investigated in numerous subtypes of human cancer, with overall controversal results. In this paper we studied the immunohistochemical expression of 3 autophagy related proteins (Beclin-1, p62 and ATG7) in a cohort of 85 primary uveal melanoma treated by primary enucleation (39 with metastasis and 46 non metastatic) and correlated their expression with clinico-pathological parameters and blood vascular microvessel density, in order to investigate the potential prognostic role of autophagy in this rare neoplasm. We found that high immunohistochemical levels of Beclin-1 correlated with a lower risk of metastasis and higher disease-free survival times, indicating a positive prognostic role for Beclin-1 in uveal melanoma. No statistically significative differences regarding the expression of ATG7 and p62 between metastatic and non metastatic patients was detected.